Electoral competition with uncertainty averse parties - Sophie Bade (Max Planck Institute for Research on Collective Goods, 2010)
The nonexistence of equilibria in models of electoral competition involving multiple issues is one of the more puzzling results in political economics. In this paper, we relax the standard assumption that parties act as expected utility maximizers. We show that equilibria often exist when parties with limited knowledge about the electorate are modeled as uncertainty-averse. What is more, these equilibria can be characterized as a straightforward generalization of the classical median voter result.
Keywords: D72; D81; 330; Uncertainty Aversion; Multiple Priors; Median Voter; Electoral Competition over many Issues; Wahlkampf; Politische Partei; Risikoaversion; Median Voter; Gleichgewicht; Theorie